Long-term treatment with eribulin in heavily pretreated women with metastatic breast cancer: a case series. (April 2017) - Morritti, Maria; Iodice, Giuseppe; Melaccio, Assunta; D'Onofrio, Loretta; Bergnolo, Paola; Boglione, Antonella; Comandone, Alessandro; Molinaro, Peppina; Garigliano, Danula
During the last decades, much effort has been made to develop and test treatments for advanced/metastatic breast cancer (MBC) able to prolong survival and improve patients' quality of life. In this regard, eribulin represents one of the most recent and interesting discoveries. This tubulin-targeting chemotherapy demonstrated a survival benefit in MBC women who progressed after at least two prior lines of chemotherapy for the treatment of metastatic disease (prior therapies should have included an anthracycline and a taxane, in either adjuvant or metastatic setting). Here, we described five cases of heavily pretreated MBC patients who experienced long-lasting control of disease with eribulin.